Analisis Niat Perilaku Anggota Komunitas Hijabers Surabaya Dalam Menggunakan Tabungan Syariah: Perspektif Theory Of Planned Behavior - Cecia Rahmadanty; Masmira Kurniawati (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2015)
A large number of muslim population in Indonesia have an impact on the development of muslim fashion in Indonesia and led to the emergence of muslim communities such as Hijabers Surabaya community. Hijabers Surabaya community also linked himself with sharia, such as cooperation with the islamic banking in which all community members will get free sharia account when joining the community.This research focuses on the behavior and attitude of community members towards the use of sharia account by using the theory of planned behavior perspective. This study used Structural Equation Model. Total participants in this study amounted to 150 members. The results obtained in this study is: (1) Behavior belief affect the attitude toward behavior. (2) Normative belief not effect the subjective norm. (3) Motivation to comply not effect the subjective norm. (4) Control belief affect the perceived behavioral control. (5) Attitude toward behavior affect the intention to use. (6) Subjective norm not affect the intention to use. (7) Perceived behavioral control not affect to the intention to use.